Neutrophil-to-lymphocyte ratio and short-term mortality in patients having anti-MDA5-positive dermatomyositis with interstitial lung disease: a retrospective study - Hongxia Xin; Ping He; Bin Xi; Zhaojun Wang; Han Wang; Faxuan Wang; Zhanbing Ma; Jing Xue; Yuanyuan Jia; Hourong Cai; Bi Chen; Juan Chen (BMC Pulmonary Medicine)
Abstract Background In this study, we aimed to explore the association between baseline and early changes in the neutrophil-to-lymphocyte ratio (NLR) and the 30-day mortality rate in patients having anti-melanoma differentiation-associated gene 5 (MDA5)-positive dermatomyositis with interstitial lung disease (DM-ILD). Methods Overall, 263 patients with anti-MDA5 DM-ILD from four centers in China were analyzed. Multivariate logistic regression analysis was used to evaluate the impact of baseline NLR on the 30-day mortality rate in patients with anti-MDA5-positive DM-ILD. Furthermore, a generalized additive mixed model (GAMM) was applied to compare the NLR variations over time between 30-day survival group and non-survival group. Results Two hundred sixty-three patients with anti-MDA5-positive DM-ILD were divided into different groups based on their NLR and whether they survived or not within 30 days. The multivariate logistic regression analysis, accounting for confounding factors, identified an elevated baseline NLR as a prognostic indicator for 30-day mortality in patients with anti-MDA5-positive DM-ILD (hazard ratio 2.68, 95% confidence interval [CI] 1.18,6.00, P = 0.019). Furthermore, the GAMM results indicated that the NLR gradually increased more in the non-survival group compared with the survival group within 14 days of admission, with a daily average increase of 1.03 (β = 1.03; 95% CI, 0.75–1.31; P < 0.001). Conclusions We found that an elevated baseline NLR and its progressive increase are associated with 30-day mortality in patients with anti-MDA5-positive DM-ILD.